Propoganda dalam Komunikasi Politik Melalui Media Sosial - Winda Kustiawan; Alfin Qodri Hafiz; Khalid Rasyidin; Putri Amelia; Sehta Jupiter Ketaren (Universitas Muhammadiyah Enrekang, 2022)
Propaganda is an important thing to support success in political communication. Basically propaganda is a persuasive communication technique, which has a greater impact than informative communication. Political communication itself is communication that leads to the achievement of an influence, so that the problems discussed by this communication activity can bind all its citizens with sanctions determined together through political institutions. Social media is a modern media whose use is as a means used by people in everyday life. Social media can quickly and widely disseminate information only through smartphone devices that are connected to the internet. Thus, social media is widely used by political activists, both as information dissemination and as messages containing propaganda, and later this will be conveyed to a wide audience who use social media.